Effect of Nurse-led Educational Interventions on Self-care of Adult Patients with Heart Failure: A Systematic Review - Reginus Tertius Malara; Syahrul Syahrul (University of Muhammadiyah Malang, 2019)
The purpose of this systematic review is to identify the effect of individual nursing-led, patient sessions on adult care with heart failure (HF) in hospitals, outpatient clinics and at home or community. A systematic review of the intervention study. Using nurse terminology, education, heart failure, self-care in the PubMed database, ScienceDirect, Willey, ProQuest. The articles in question are related to educational interventions by individual nurses to patients with management of heart failure. The results of this review identified nursing-led education sessions to adults with heart failure proven to improve self-care abilities. These results suggest that the education of patients led by nurses to adult patients with heart failure improves self-care. Education led by nurses delivered in hospitals, outpatient and in-home clinics using diverse methods have an impact on improving self-care.